Antinomies of Modernity : Essays on Race, Orient, Nation - Mazumdar, Sucheta, 1948-; Kaiwar, Vasant, 1950- (Book collections on Project MUSE., 2003)
A collection of essays arguing for a global and economically based modernity driven by capitalist development.